Crisis standards of care in a pandemic: navigating the ethical, clinical, psychological and policy-making maelstrom. (14th August 2020) - Hertelendy, Attila J; Ciottone, Gregory R; Mitchell, Cheryl L; Gutberg, Jennifer; Burkle, Frederick M
Abstract: The COVID-19 pandemic has caused clinicians at the frontlines to confront difficult decisions regarding resource allocation, treatment options and ultimately the life-saving measures that must be taken at the point of care. This article addresses the importance of enacting crisis standards of care (CSC) as a policy mechanism to facilitate the shift to population-based medicine. In times of emergencies and crises such as this pandemic, the enactment of CSC enables concrete decisions to be made by governments relating to supply chains, resource allocation and provision of care to maximize societal benefit. This shift from an individual to a population-based societal focus has profound consequences on how clinical decisions are made at the point of care. Failing to enact CSC may have psychological impacts for healthcare providers particularly related to moral distress, through an inability to fully enact individual beliefs (individually focused clinical decisions) which form their moral compass.